1993
DOI: 10.1016/0248-4900(93)90124-w
|View full text |Cite
|
Sign up to set email alerts
|

Role of calcium during release of mollusc oocytes from their blocks in meiotic prophase and metaphase

Abstract: Bivalve oocytes constitute an excellent model to study the mechanisms which control cell division, since they arrest at different stages of tile meiotic process and respond quite synchronously to various external signals regulating their evolution. Different situations were observed, according to the species, which required a more careful analysis. For example, the same serotonin (5-HT) signal was found to drive prophase-arrested oocytes of Spisula to the female pronucleus stage, whereas Ruditapes oocytes stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…sampling was carried out after 0, 2,4.6, 8,9, 10, 11, 12, 14, 16 h for A carterue and 0. 1,2,3,4,5,6,7,8,10,12 h for T weissflogii.…”
Section: Dinojlagellate and Diatommentioning
confidence: 99%
“…sampling was carried out after 0, 2,4.6, 8,9, 10, 11, 12, 14, 16 h for A carterue and 0. 1,2,3,4,5,6,7,8,10,12 h for T weissflogii.…”
Section: Dinojlagellate and Diatommentioning
confidence: 99%
“…17 and 18). eEF-2 kinase activity is found in virtually all mammalian tissues as well as in various invertebrate organisms (19). eEF-2 kinase phosphorylates eEF-2 at two threonine residues that are conserved in all eukaryotes and are located within a GTP-binding domain (17,18).…”
mentioning
confidence: 99%
“…The molecular cascade, and the underlying genes involved in this phenomenon, has been little studied in bivalves showing mainly the crucial role of Ca 2+ signaling pathway during oocyte maturation (e.g. ; Abdelmajid et al 1993;Colas and Dubé 1998;Deguchi and Morisawa 2003;Leclerc et al 2000;Stricker and Smythe 2001;Zhang et al 2009). It has been suggested that continuously synthesized, short-lived proteins are responsible for maintaining metaphase arrest in some molluscan oocytes, with cyclin regulatory proteins as good candidates since their disappearance triggered A C C E P T E D M A N U S C R I P T metaphase/anaphase transition and polar body extrusion (Colas and Dubé 1998).…”
Section: Prophase I Block and Meiotic Maturation In Ruditapes Decussamentioning
confidence: 99%
“…Ruditapes and other molluscs, calcium may act via a calcium calmodulin-kinase since calcium calmodulin antagonists were able to prevent metaphase I release and cyclin degradation upon fertilization (Abdelmajid et al 1993;Colas and Dubé 1998;Leclerc et al 2000;Whitaker 1996;Zhang et al 2009). In this work we found the enzyme Calcium/calmodulin-dependent 3',5"-cyclic nucleotide phosphodiesterase 1C (Cam-PDE1C) (FC=1.7) among the genes more abundant in good quality oocytes.…”
Section: Prophase I Block and Meiotic Maturation In Ruditapes Decussamentioning
confidence: 99%